To Examine the Interventions by Development Partners in Supporting the Growth and Development of Commercial Enterprises in Lira District, Northern Uganda - Eton, Marus; Mwirumubi, Richard; Edaku, Charles (European Journal of Business and Management, 2017)
The development of entrepreneurship has motivated majority of Ugandans to start commercial enterprises (CEs) as a source of employment and economic growth. The objective of the study was to examine the various intervention employed by development partners in supporting the growth and development of commercial enterprises in Lira District, Northern Uganda. Using purposive and simple random sampling procedure, a sample of 274 participants was selected for the survey. A self administered questionnaire was structured. The data were analyzed using SPSS statistical package. The study recommended that development partners operating in the district should consider supporting commercial enterprise (CE) in advocating for policy reforms, providing financial support, creation business information center where entrepreneurs could access business information at affordable rates and supporting technological development to support creativity and innovations.
Keywords: Policy reforms; Financial support; Business Information and Technological support.